2008
DOI: 10.1089/acm.2007.7117
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Rhodiola rosea (Rhodax®) for Generalized Anxiety Disorder (GAD)

Abstract: Significant improvement in GAD symptoms was found with R. rosea, with a reduction in HARS scores similar to that found in clinical trials. These preliminary findings warrant further exploration of treatment with R. rosea in clinical samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 32 publications
1
41
0
2
Order By: Relevance
“…Several clinical trials have shown that SHR-5 improved mental performance and attention in cognitive function in fatigue after single and repeated administration [44, 53, 54], and prevented physical, emotional, and mental exhaustion in patients with fatigue syndrome [43]. SHR-5 was also shown to be effective in the treatment of mild to moderate depression [42] and generalized anxiety [54, 55] in clinical trials. Due to the rapidly growing demand for Rhodiola-based products on the market during a past few years, Rhodiola has been considered to be endangered plant species in many countries [16].…”
Section: Rhodiola Rosea L and Its Active Componentsmentioning
confidence: 99%
“…Several clinical trials have shown that SHR-5 improved mental performance and attention in cognitive function in fatigue after single and repeated administration [44, 53, 54], and prevented physical, emotional, and mental exhaustion in patients with fatigue syndrome [43]. SHR-5 was also shown to be effective in the treatment of mild to moderate depression [42] and generalized anxiety [54, 55] in clinical trials. Due to the rapidly growing demand for Rhodiola-based products on the market during a past few years, Rhodiola has been considered to be endangered plant species in many countries [16].…”
Section: Rhodiola Rosea L and Its Active Componentsmentioning
confidence: 99%
“…Despite its excellent safety profile, golden root might be not suitable for patients with bipolar spectrum disorders because of its activating effect, which could increase patients' risk of cycling (Iovieno et al, 2011). In addition, the most common side effects of golden root involve irritability and insomnia (Bystritsky et al, 2008). Minor effects on CYP3A4 and p-glycoprotein were reported (Hellum et al, 2010).…”
Section: Golden Root (Rhodiola Rosea)mentioning
confidence: 99%
“…Several traditional herbal medicines, such as Valeriana officinalis ,[9394] Passiflora incarnata ,[9596] Matricaria recutita L.,[9798] Humulus lupulus ,[99100] Ginkgo bibola ,[101] Centella asiatica ,[102] Rhodiola rosea ,[103] Hypericum perforatum ,[104] Piper methysticum [105106] and Zizyphus jujuba [14] have been widely clinically reported to improve sleep and other mental disorders. Moreover, recently Wuling capsule, a single herb formula from mycelia of precious Xylaria nigripes was investigated for its efficacy and safety, through a multicenter, randomized, double-blind, placebo-controlled trail, in Chinese patients with insomnia.…”
Section: Clinical Studies Done On Polygonum Multiflorum And/or Its Bimentioning
confidence: 99%